Ответы и объяснения

2013-07-14T16:13:09+04:00

a) 0.2^9 * 5^7 = 5^(-9) * 5^7 = 5^(-2) = 1/25

b) 0.4^10 * 2.5^12 = 2.5^(-10) * 2.5^12 = 2.5^2 = 6.25

c) 0.2^6 * 25^3 = 5^(-6) * 5^6 = 5^0 = 1

d) (1/9)^6 * 81^4 = 9^(-6) * 9^8 = 9^2 = 81

Лучший Ответ!
2013-07-14T16:29:55+04:00

Немного теории:

 

a^0=1\\\\(\frac{a}{b})^n=\frac{a^n}{b^n}\\\\ a^n\cdot a^m=a^{n+m}\\\\ \frac{a^n}{a^m}=a^{n-m}\\\\ B^n=b^n\cdot b^n \ => 25^2=5^2\cdot 5^2\\ B^n=x^n\cdot y^n \ => 10^2=2^2\cdot 5^2

 

 

в) 0,2^9\cdot 5^7=(\frac{2}{10})^9\cdot (\frac{5}{1})^7=\frac{2^9\cdot 5^7}{10^9\cdot 1^7}=\frac{2^9\cdot 5^7}{2^9\cdot 5^9\cdot 1}=2^0\cdot 5^{7-9}\cdot 1=\\ =1\cdot 5^{-2}\cdot 1=\frac{1}{5^2}=\frac{1}{25} 

 

г) 0,4^{10}\cdot 2,5^{12}=\frac{4^{10}}{10^{10}}\cdot \frac{25^{12}}{10^{12}}=\frac{2^{10}\cdot 2^{10}\cdot 5^{12}\cdot 5^{12}}{2^{10}\cdot 5^{10}\cdot 2^{12}\cdot 5^{12}}=\frac{2^{20}\cdot 5^{24}}{2^{22}\cdot 5^{22}}=\\ =2^{20-22}\cdot 5^{24-22}=2^{-2}\cdot 5^2=\frac{1}{2^2}\cdot 25=\frac{25}{4}=6,25

 

д) 0,2^6\cdot 25^3=\frac{2^6\cdot 25^3}{10^6\cdot 1^3}=\frac{2^6\cdot 5^3\cdot 5^3}{2^6\cdot 5^6\cdot 1}=\frac{2^6\cdot 5^6}{2^6\cdot 5^6}=2^{6-6}\cdot 5^{6-6}\cdot=2^0\cdot 5^0=1

 

е) (\frac{1}{9})^6\cdot 81^4=\frac{1^6\cdot 81^4}{9^6\cdot 1^4}=\frac{1\cdot 9^4\cdot 9^4}{9^6\cdot 1}=\frac{9^8}{9^6}=9^{8-6}=9^2=81